Clinical Usefulness of SISCOM-SPM Compared to Visual Analysis to Locate the Epileptogenic Zone - Oliveira Young, Carla; Etchbehere, Elba C. S. C.; Souza, Edna Marina; Brunetto, Sergio Querino; Santos, Allan de Oliveira; Lima, Mariana C. L.; Ortiz-De la Rosa, Sebastian; Alvim, Marina; Yasuda, Clarissa Lin; Ramos, Celso Darío; Cendes, Fernando; Amorim, Barbara Juarez (Frontiers in Neurology, 2020)
Introduction: Subtraction of ictal-interictal SPECT co-registered to MRI (SISCOM) is a quantification tool that can improve the sensitivity and specificity of the epileptogenic zone (EZ) localization. Commercially available image analysis software packages for SISCOM are costly, and Statistical Parametric Mapping (SPM) could be an alternative free software. Aim: To compare SISCOM-SPM versus visual analysis for localization of the EZ in patients with pharmacoresistant focal epilepsies. Materials and methods: We evaluated all our patients with focal epilepsies that underwent ictal and interictal SPECT. We defined the reference standard to locate the EZ by pathology and follow-up (in patients submitted to surgery), or seizure semiology, serial EEG, long-term-video-EEG, 18F-FDG PET/CT and MRI (in patients who were not operated). We compared the location of the EZ by visual analysis of SPECT images and by SISCOM-SPM to the reference standard and classified as concordant, discordant, or partially concordant. Results: We included 23 patients. Visual analysis was concordant with the EZ reference standard in only 13 patients (56.5%), while SISCOM-SPM was concordant in 18 cases (78.3%), providing a 21.8% increase in the location of EZ. However, this difference was not significant due to the small sample size (p = 0.0856). Conclusion: Our preliminary results demonstrate that, in clinical practice, SISCOM-SPM has the potential to add information that might help localize the EZ compared to visual analysis. SISCOM-SPM has a lower cost than other commercially available SISCOM software packages, which is an advantage for developing countries. Studies with more patients are necessary to confirm our findings.